Reviving external cephalic version: a review of its efficacy, safety, and technical aspects - Gwang Jun Kim (Korean Society of Obstetrics and Gynecology, 2019)
Currently, the rate of cesarean sections being performed in Korea is approximately 40%, with Korea ranking 4th among the Organization for Economic Co-operation and Development countries with respect to cesarean deliveries. Breech presentation at term is an important indication for cesarean section among other factors, including medicolegal concerns and pregnancies in women of advanced maternal age. Term breech presentation is associated with a higher fetal mortality rate than that associated with a cephalic presentation. Therefore, in Korea, most of these women deliver by cesarean section to avoid the complications of vaginal breech delivery. However, cesarean section is itself associated with considerable obstetric morbidity and sometimes, mortality. External cephalic version (ECV) is a useful method to reduce the cesarean section rate in women with breech presentation and therefore to reduce the incidence of breech presentation at delivery. Studies have shown that routine use of ECV reduces the cesarean section rate by approximately two-thirds in term pregnancies with breech presentation. ECV is accepted as a safe, efficacious, and cost-effective method and is recommended by both the American College of Obstetricians and Gynecologists and the Royal College of Obstetricians and Gynecologists in all pregnancies with term breech presentation, if not contraindicated. In Korea, although most clinicians are aware of the option of ECV, their relative lack of experience in performing the procedure and fear of complications render them hesitant to perform ECV. This review is aimed at guiding obstetricians by describing the efficacy, safety concerns, and technical aspects of this procedure.